2014
DOI: 10.1177/0748233714555388
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal exposure to single-wall carbon nanotubes on reproductive performance and neurodevelopment in mice

Abstract: Carbon nanotubes with extraordinary properties may become a novel drug and gene delivery tool in nanomedicine; however, insufficient information is available regarding their biosafety. Therefore, this work was performed to study the effect of prenatal exposure of single-walled carbon nanotubes (SWCNTs) on reproductive and neurobehavioral endpoints in mice. Thirty pregnant female mice were assigned to three groups (n = 10 for each group). The two treated groups were injected intraperitoneally (i.p.) with 1 or 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
(51 reference statements)
1
9
0
Order By: Relevance
“…We recently showed that mouse offspring of mothers that were i.p. exposed to 10 mg kg À1 pristine SWNTs identical to SWNTs used in the present study were overtly anxious but showed similar locomotor activity compared to control pups in EPM (Ivani et al, 2014). To the best of our knowledge, the molecular mechanisms that govern anxiogenic effects of CNTs have not been reported.…”
Section: Discussionmentioning
confidence: 57%
“…We recently showed that mouse offspring of mothers that were i.p. exposed to 10 mg kg À1 pristine SWNTs identical to SWNTs used in the present study were overtly anxious but showed similar locomotor activity compared to control pups in EPM (Ivani et al, 2014). To the best of our knowledge, the molecular mechanisms that govern anxiogenic effects of CNTs have not been reported.…”
Section: Discussionmentioning
confidence: 57%
“…The metric qualities of the tests are satisfactory or good. They have a good sensitivity and they discriminate subtle differences in environment (Carlier, Roubertoux, & Cohen‐Salmon, ; Dulioust et al., ) and in drug exposure (Ivani, Karimi, Tabatabaei, & Syedmoradi, ). Many publications confirm that genetic events impact the behaviors that are measured by the tests (Willing & Wagner, ).…”
Section: Introductionmentioning
confidence: 93%
“…The behavioral assessment of the offspring (Smart and Dobbing, 1971;Chiavegatto et al, 1997;Chen et al, 2012;Ivani et al, 2016) was conducted as follows. The number, the weights, and the changes in weight of the pups for each dam were recorded and analyzed statistically.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…The physical development and the maturation of the pups were evaluated using the methodology proposed by Smart and Dobbing (1971), Chiavegatto et al (1997), Chen et al (2012), and Ivani et al (2016). First, the dates on which surface righting reflexes occurred were recorded (Ivani et al, 2016), with the test performed during postnatal days (PNDs) 4-21, by gently placing the pup in a supine position and observing whether it could right itself and bring all four of its limbs into contact with the surface within 3 s. Those that succeeded were considered to have met the standard. Next, the dates of eye opening (beginning during PNDs 10-16), incisor eruption (beginning on PND 11), and ear opening (beginning on PND 15) were noted.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation